Impacts of longitudinal water curtain cooling system on transcriptome-related immunity in ducks - Qian Hu; Tao Zhang; Hua He; Fajun Pu; Rongping Zhang; Liang Li; Jiwei Hu; Lili Bai; Chunchun Han; Jiwen Wang; Hehe Liu (BMC Genomics, 2024)
Abstract Background The closed poultry houses integrated with a longitudinal water curtain cooling system (LWCCS) are widely used in modern poultry production. This study showed the variations in environmental conditions in closed houses integrated with a longitudinal water curtain cooling system. We evaluated the influence of different environmental conditions on duck growth performance and the transcriptome changes of immune organs, including the bursa of Fabricius and the spleen. Result This study investigated the slaughter indicators and immune organ transcriptomes of 52-day-old Cherry Valley ducks by analyzing the LWCC at different locations (water curtain end, middle position, and fan cooling end). The results showed that the cooling effect of the LWCCS was more evident from 10:00 a.m. -14:00. And from the water curtain end to the fan cooling end, the hourly average temperature differently decreased by 0.310℃, 0.450℃, 0.480℃, 0.520℃, and 0.410℃, respectively (P < 0.05). The daily and hourly average relative humidity decreased from the water curtain end to the fan cooling end, dropping by 7.500% and 8.200%, respectively (P < 0.01). We also observed differences in production performance, such as dressing weight, half-eviscerated weight, skin fat rate, and percentage of abdominal fat (P < 0.01), which may have been caused by environmental conditions. RNA-sequencing (RNA-seq) revealed 211 and 279 differentially expressed genes (DEGs) in the ducks’ bursa of Fabricius and spleen compared between the water curtain end and fan cooling end, respectively. The Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis of the two organs showed the DEGs were mainly enriched in cytokine-cytokine receptor interaction, integral component of membrane, Retinoic acid-inducible gene I (RIG-I)-like receptors (RLRs) signaling pathway, etc. Our results implied that full-closed poultry houses integrated with LWCCS could potentially alter micro-environments (water curtain vs. fan cooling), resulting in ducks experiencing various stressful situations that eventually affect their immunity and production performance. Conclusion In this study, our results indicated that uneven distributions of longitudinal environmental factors caused by LWCCS would affect the dressed weight, breast muscle weight, skin fat rate, and other product performance. Moreover, the expression of immune-related genes in the spleen and bursa of ducks could be affected by the LWCCS. This provides a new reference to optimize the use of LWCCS in conjunction with close duck houses in practical production.